Programa de educación financiera en la parroquia “Amaluza” del cantón Espíndola. - Álvarez Jiménez, Luisa Fernanda (2024)
Financial education is aimed at understanding financial concepts and developing skills in this area in order to make better, informed and accurate decisions. The objective of this research is to design a financial education programme for the inhabitants of the parish of "Amaluza" in the canton of Espíndola. The study had a mixed approach of exploratory, descriptive and experimental scope. The population of 334 people from the parish of Amaluza, between the ages of 15 and 64 years, was included under the criteria of the Economically Active Population (EAP), and began with the assessment using the methodology used by the PISA programme, which classifies financial knowledge into five levels. The results were divided into two stages. In the first stage, an evaluation was carried out which showed that, prior to the training, the general population was at level two; with these limitations, a financial education programme was designed with relevant topics, which, once applied, the inhabitants increased their level of financial knowledge, reaching level five. In conclusion, it was determined that the programme was efficient and helped to improve the level of financial knowledge of the people on financial issues to improve the management of their economic resources.